Residual strength of additive manufactured ABS parts subjected to fatigue loading. (May 2020) - Ziemian, C.W.; Ziemian, R.D.
Graphical abstract: Highlights: Fiber orientation and layering pattern affect strength degradation of fatigue loaded FDM parts. Rate of normalized strength degradation is higher for 0° parts than bidirectional mesostructures. Normalized residual strengths of bidirectional parts are greater than that of 0° parts. A nonlinear phenomenological model predicts residual strength for the studied factor levels. Abstract: This study investigates the effect of tension fatigue loading on the residual strength degradation of additive manufactured ABS components formed by fused deposition modeling. Sinusoidal tension-tension fatigue loading with nine treatment combinations of cycling stress and duration were followed by tensile tests for 0°, +45/−45°, and +30/−60° mesostructures. Normalized residual strengths of the bidirectional mesostructures were significantly higher than that of the 0° parts for all factor combinations studied. A proposed phenomenological model, based on a strength degradation model for carbon fiber-reinforced composites, successfully described 92–96% of residual strength variability for the 0° specimens, and 77–92% for the bidirectional mesostructures tested.